ANALISIS PENGARUH KONSENTRASI AUDITOR, INDEPENDENSI DEWAN KOMISARIS DAN UKURAN KOMITE AUDIT TERHADAP PENETAPAN FEE AUDIT EXTERNAL (STUDI EMPIRIS PADA PERUSAHAAN IDX BUMN20 PERIODE 2015-2019) - Yonatan Alfino; Valentine Siagian (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
ABSTRACT This research aims to analyze the effect of auditor concentration, board independence, and audit committee size on the determination of audit fees. Samples were obtained in this research was the IDX BUMN20 (top twenty constituents) contained in the IDX BUMN20 Index Fact Sheet as of December 2019 during the 2015-2019 period. The analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear regression test, and coefficient of determination test. Test results of the independent variable, level of auditor concentration, have a significant positive effect on the determination of audit fees, the independence of the Board of Commissioners has a negative but insignificant effect on the dependent variable on audit fees, and the size of the Audit Committee has a positive but insignificant effect on the dependent variable on audit costs. The result of the determination coefficient is 64.2%, which means that the independent variable affects the dependent variable by 64.2%. Keywords: Auditor Concentration, Board of Commissioners Independence, Audit Committee Size, Audit Fee